Genetic Parameter Evaluation on Advanced Generations of A Cross to Improve Magelang Local Black Rice Cultivars - Setyorini Widyayanti; Panjisakti Basunanda; Suyadi Mitrowihardjo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
Evaluating genetic selection parameters of a cross between a local blackgrained rice cultivar from Magelang and an improved rice cultivar ‘Situbagendit’ is necessary to check the efffectiveness of selection in advanced generations, i.e. F4, F5 and F6 generation. The objective of this study was to compare and evaluate changing in several genetic parameters of the generations so that we can assess the selection effectiveness. Randomly picked 48 lines of F4, F5 and F6 generation, respectively, along with their parents, were evaluated on a farmer’s field in Pakem, Yogyakarta from May until September 2016. The experiment was arranged in an incomplete randomized design with two replications. Seed of each F4, F5 and F6 lines with their parents were planted in 1 m × 2 m plot, with 20 cm × 20 cm plant spacing. For each plot 40 individuals were planted. The agronomic characters were evaluated: plant height, productive tillers, pericarp color, full grains, empty grains, weight of 1000 seeds, days to flowering and days to maturing. Genetic variances, heritability and expected genetic gain among and within family from the advanced generations were evaluated and compared. Results showed that heritability and genetic gains value whether from selected or unselected generation need more emphasis on within family selection especially in generative (full grains, empty grains and weight of 1000 seed) characters.